How kidneys work? Developing of Android-based Adobe animate media for senior high school students - Indrawan Prasetyo; Ainur Rofieq; S. Sukarsono; Tutut Indria Permana (Research and Development in Education (RaDEn), 2022)
Media is one of the determining factors for learning success which can accommodate student critical thinking. Moreover, during the COVID-19 pandemic, learning media became crucial in online learning. This study aims to produce and test the feasibility of android-based media on kidney material developed through Adobe Animate CC software. In addition, it also to find the effectiveness of the media in improving the critical thinking skills of eleventh graders students when used in online learning. Borg & Gall's model was used in this research and development but was limited to the seventh stage. Data collection techniques used interviews, validation (media and material experts), and test. The instruments used are interview sheets, validation sheets, response questionnaires, and essays (five critical thinking questions). The test subjects were 15 senior high school students in Bantur, East Java, Indonesia. The validation results from media and material experts show that the media is "very feasible" to use. Teachers and students stated that the media was "very practical" in online learning. There is a significant difference between students' critical thinking skills before and after using the media, t(14) = 5.65, p < 0.001. The study finding becomes the basis for continuing the process of media dissemination.